The Support of Exclusive Breastfeeding on Adolescent Mothers - Sukati Sarmin; Ismarwati (International Journal of Advanced Science and Technology, 2020)
Breastmilk is the main source of food for infants who have not been able to consume solid food. Giving of Breastmilk is one of the important strategies for reducing mortality and malnutrition in infants and toddlers [1]. The World Health Organization (WHO) has recommended the introduction of exclusive breastfeeding in newborns up to the first six months and no additional food or other liquids except vitamins and medicines [2]. The method used in this scoping review was the Arksey and O ’Malley guidelines. The findings of the 9 articles conducted a review of the types of support in the giving of exclusive breastfeeding include social support, information, instrumental, emotional, appreciation and networking. The barriers to giving exclusive breastfeeding support are the perception of mothers on breastfeeding, the impossibility to breastfeed, lack of knowledge and understanding of Breastmilk and work. The theme found in this review is the types of support in giving exclusive breastfeeding and barriers to provide exclusive breastfeeding support.